Secondary metabolites of rhizospheric fungal isolate Aspergillus carneus ABRF4 regulate the antibacterial and anti-proliferative activity against cancer cells - MAHENDRA KUMAR SAHU; RAGINI YEERAVALLI; AMITAVA DAS; HARIT JHA (Nusantara Bioscience, 2023)
Abstract. Sahu MK, Yeeravalli R, Das A, Jha H. 2023. Secondary metabolites of rhizospheric fungal isolate Aspergillus carneus ABRF4 regulate the antibacterial and anti-proliferative activity against cancer cells. Nusantara Bioscience 15: 137-142. The medicinal capabilities of plants are influenced by soil chemistry, genotype, and climate. Many biotic and abiotic factors affect soil composition. Microorganisms constituting the soil microflora indicate a mutualistic relationship with plant rhizospheric region, and they play an important role in plant secondary metabolite production, yield, and efficacy. They are the major resources for structurally unique bioactive natural metabolites. The aim of the present study was to evaluate the bioactivity of the secondary metabolite extracted from the rhizospheric fungal isolate Aspergillus carneus ABRF4) isolated from the Achanakmar Biosphere Reserve, Chhattisgarh, India. The fungal secondary metabolites were extracted using several solvents by soxhlet extraction techniques. The crude and partially purified column fractions of A. carneus ABRF4 were characterized by Gas Chromatography-Mass Spectroscopy (GC-MS), Fourier Transform Infra-Red (FTIR) spectrum, and Thin Layer Chromatography (TLC). Results showed that the acetonitrile fraction had an antimicrobial activity with the variable zone of inhibition against human pathogens such as Bacillus circulans (MTCC-7906), Bacillus subtilis (MTCC 441), Staphylococcus aureus (MTCC-96), and Ralstonia eutropha (MTCC-2487). The crude extracts and the identified secondary metabolite, trans- 1,3-dimethyl-Cyclohexane, possess different anti-proliferative activity against human tissue-specific cancer cell lines, including breast cancer (MDA-MB-231, MDA-MB-468, and MCF-7), liver cancer (HepG2), lung cancer (A-549), and prostate cancer (DU-145) suggesting a potential therapeutic application of the isolated rhizospheric fungi.